2020
DOI: 10.1111/ajt.15910
|View full text |Cite
|
Sign up to set email alerts
|

Human leukocyte antigen selected allogeneic mesenchymal stromal cell therapy in renal transplantation: The Neptune study, a phase I single-center study

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 31 publications
(68 reference statements)
3
53
0
Order By: Relevance
“…The development of anti‐HLA antibodies was not reported in a recent study where HLA selected allogeneic MSC were infused with low‐dose tacrolimus [39]. This design was proven to be safe with a follow‐up of 1 year after transplantation [40]. In this study, no major alterations in T‐ and B‐cell populations or plasma cytokines were observed upon MSC infusions.…”
Section: Mesenchymal Stromal Cell Therapiesmentioning
confidence: 62%
See 3 more Smart Citations
“…The development of anti‐HLA antibodies was not reported in a recent study where HLA selected allogeneic MSC were infused with low‐dose tacrolimus [39]. This design was proven to be safe with a follow‐up of 1 year after transplantation [40]. In this study, no major alterations in T‐ and B‐cell populations or plasma cytokines were observed upon MSC infusions.…”
Section: Mesenchymal Stromal Cell Therapiesmentioning
confidence: 62%
“…It is advised to document the (serious) adverse events (SAE) according to MedDRA ® (Medical Dictionary for Regulatory Activities), which is the international medical terminology developed under the auspices of the International Council for Harmonization of Technical Requirements for Pharmaceuticals for Human Use. This method has been used in two recently published trials with cell therapy in renal transplantation and allows for comparison between trials [40,58]. Since the development of infections and malignancies may take time, long‐term follow‐up of patients is required after finalizing clinical trials.…”
Section: Endpoints and Monitoring Of Cellular Therapiesmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, hBMMSC-EVs revealed significant improvements in patients suffering from refractory graft-versus-host disease [ 179 ]. In another study, administration of hUCMSC-EVs resulted in overall improvement in patients with grade III-IV chronic kidney disease [ 180 ]. Nassar et al conducted a clinical trial to assess the effects of hUCMSC-EVs on pancreatic islet beta cell mass in Type-1 diabetic patients (NCT02138331).…”
Section: Attempts To Improve the Therapeutic Outcomes Of Mscsmentioning
confidence: 99%